Foodborne Pathogens Across Different Food Matrices in Sicily (Southern Italy) - Valeria Blanda; Ilenia Giacchino; Valeria Vaglica; Vanessa Milioto; Sergio Migliore; Santina Di Bella; Francesca Gucciardi; Carmelo Bongiorno; Giuseppina Chiarenza; Cinzia Cardamone; Isabella Mancuso; Maria Luisa Scatassa; et al. (Pathogens)
Foodborne diseases result from the consumption of foods contaminated with pathogens or their toxins and represent a serious public health problem worldwide. This study aimed to assess the presence of Rotavirus (RoV), Adenovirus (AdV), Norovirus (NoV), Hepatitis A and Hepatitis E viruses (HAV and HEV, respectively), Toxoplasma gondii, Coxiella burnetii and Leptospira spp. across various food matrices in Sicily. The analysis concerned 504 samples, including mussels, farmed meat, game meat, vegetables and bulk milk. Following appropriate pre-treatment, acid nucleic extraction was carried out and amplification of pathogen nucleic acids was carried out by molecular methods. The mussels tested positive for NoVs (3/51, 5.9%) and farm meat resulted positive for T. gondii (1/34, 2.9%). The game offal samples tested positive for HEV, which was detected in 17 out of 222 samples (7.7%), and T. gondii (18/318, 5.7%) and Leptospira spp. (2/318, 0.6%). The milk samples tested positive for C. burnetii (15/85, 17.6%), T. gondii (2/85, 2.4%) and Leptospira spp. (1/85, 1.2%). This study highlights the variability in the risk of contamination of different food matrices, confirming the importance of vigilance in the consumption of potentially contaminated food products.